Mangroves of Kerala, lndia - Anupama, C.; Sivadasan, M. (Rheedea, 2004)
The present study reports 15 true mangrove and 49 mangrove associate species from Kerala coast. True mangrove species belonged to nine genera under seven families. Detailed descriptions, illustrations, notes on distribution and updated nomenclature of the true mangrove species are provided. Mangrove associates are listed. Five true mangrove species earlier reported from Kerala viz.: Bruguiera eriopetala , B. malabarica , B. parviflora and Ceriops tagal could not be located during the present investigation. Bruguiera gymnorrhiza, B. sexangula, Excoecaria indica, Lumnitzera racemosa and Sonneratia alba are found very rare along Kerala coast. Developmental and anthropogenic activities, grazing and widespread prawn farming are the major threats to Kerala mangroves.